2011
DOI: 10.1590/s1983-14472011000100002
|View full text |Cite
|
Sign up to set email alerts
|

A atenção pré-natal na ótica de um grupo de mulheres usuárias do subsetor suplementar

Abstract: This qualitative approach study, aimed at understanding the perception of women who went through the Prenatal Care Attention (PCA), on the context of the Supplementary Subsector (SS), in relation to the quality of this attention. Data were collected through semi-structured interviews and analyzed by descriptive categorization. For the interviews, the PCA was considered of good quality, meeting the women's needs and exzpectations. Receptivity, bonding with the expert the consequently transmitted safety feeling … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0
2

Year Published

2013
2013
2018
2018

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 7 publications
1
5
0
2
Order By: Relevance
“…7,8,[13][14][15] The women interviewed in the present study mentioned the clarification of questions as a positive factor for the quality of prenatal care, as observed in other studies. 13,14 The presence of dialogue and instructions on health care led to a more adequate follow-up of pregnancy.…”
Section: Discussionsupporting
confidence: 84%
See 2 more Smart Citations
“…7,8,[13][14][15] The women interviewed in the present study mentioned the clarification of questions as a positive factor for the quality of prenatal care, as observed in other studies. 13,14 The presence of dialogue and instructions on health care led to a more adequate follow-up of pregnancy.…”
Section: Discussionsupporting
confidence: 84%
“…15 Professionals' awareness of the fears and anxieties of pregnant women promotes their bond with these women, which can help to prevent problems. 8 A study performed in Southern Brazil indicated that respect for pregnant women's beliefs and singularities strengthens this bond and helps professionals to meet their actual demands for primary care. 7 Studies have shown that professional guidance provided during prenatal care consultations is precarious, although such consultations are understood as privileged space for pregnant women to receive instructions about pregnancy and delivery.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This assumption was shown to condition women to choose operative parturition, to the detriment of which would be per se a preparation for natural childbirth and, logically, from undergoing normal parturition (19)(20)(21) .…”
Section: Rev Esc Enfermmentioning
confidence: 99%
“…1 Para que seja oferecida assistência de qualidade, faz-se necessário entender o que as gestantes sentem a respeito do atendimento oferecido, exercer o acolhimento, desenvolver vínculos e proporcionar as orientações necessárias, de modo que elas possam compreender essas informações. 2 A satisfação do usuário/cliente é o feedback positivo que ele dá ao serviço de saúde do hospital quando ele é objeto de assistência de qualidade não associada exclusivamente aos profissionais, mas também às condições estruturais e físicas da unidade, à qualidade da refeição oferecida, quadro de funcionários, organização do sistema, assim como às ações/serviços oferecidos desde a admissão à alta hospitalar. Desse modo, uma assistência de qualidade é considerada ferramenta de marketing, por ser uma forma de gerar satisfação.…”
Section: Introductionunclassified